PROJECT BASED LEARNING (PJBL) DALAM MENINGKATKAN KOMUNIKASI MATEMATIS SISWA - Anggalia, Fransisca (UNISAN JURNAL, 2025)
This study aims to determine the effect of Project Based Learning (PjBL) on students mathematical communication skills. This research uses a mixed methods approach, combining quantitative and qualitative methods. The quantitative approach was conducted through a pretest–posttest design to measure the improvement of students mathematical communication skills, while the qualitative approach involved observations, interviews, and documentation to describe the learning process and student activities during the implementation of PjBL. The results showed that the implementation of PjBL had a positive effect on students mathematical communication skills. Posttest scores were higher than pretest scores, N-Gain. Observations and interviews indicated that students became more active, communicative, and confident in expressing mathematical ideas, as well as capable of using mathematical symbols and representations accurately. Project documentation also showed improvements in the quality of students mathematical communication, both in written and oral forms. Based on these results, it can be concluded that Project Based Learning (PjBL) is effective in enhancing students mathematical communication skills, improving both learning outcomes and the quality of the learning process.